2007
DOI: 10.1051/forest:2007035
|View full text |Cite
|
Sign up to set email alerts
|

Influence de la méthode de fertilisation sur la mycorhization contrôlée de deux espèces de Pins méditerranéens

Abstract: -The influence of the fertilisation method: soluble (SF) vs. slow-release fertiliser (SRF) and of inoculation with Laccaria laccata (Scop.) Fr., Pisolithus tinctorius (Pers.) Coker & Couch and Melanogaster ambiguus (Vittad.) Tul & C. Tul. on ectomycorrhizal colonization and growth of Pinus pinea L. and Pinus pinaster Ait. was evaluated. For both pines, mycorrhization with L. laccata was not affected by the fertilisation method. Percentages of ectomycorrhizas (ECM) formed by P. tinctorius were dependent on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 35 publications
1
25
0
4
Order By: Relevance
“…Previously, P. tinctorius was found to be sensitive to high N fertilization (Rincón et al, 2007b). Tolerance to N may correspond to a distinct enzymatic activity that implies a different substrate exploitation method (Taniguchi et al, 2008) and could be one of the factors regulating the distribution of ECM fungi in poor or rich N forests.…”
Section: Effect Of N Fertilization On Mycorrhizal Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, P. tinctorius was found to be sensitive to high N fertilization (Rincón et al, 2007b). Tolerance to N may correspond to a distinct enzymatic activity that implies a different substrate exploitation method (Taniguchi et al, 2008) and could be one of the factors regulating the distribution of ECM fungi in poor or rich N forests.…”
Section: Effect Of N Fertilization On Mycorrhizal Developmentmentioning
confidence: 99%
“…Negative inoculation x fertilization interactions were found, so mycorrhizal effects appeared only at low fertilization, whereas high fertilization eliminated these effects. Interactive effects between fertilization and mycorrhization are frequent (Hilszanska et al, 2008;Parladé et al, 2003;Rincón et al, 2005;2007b;Smith and Read, 1997) and are attributed to the large amount of carbohydrates that the fungus requires to establish symbiosis (Dosskey et al, 1991). This justifies the detrimental effects of the mycorrhiza observed, particularly on the P. tinctorius 3SR strain which reached the highest root colonization levels.…”
Section: Effect Of Inoculation On Plant Growth and Nutritionmentioning
confidence: 99%
“…In nursery experiments, high fertilisation levels have been found to inhibit the formation of ectomycorrhizas of many fungal species including T. melanosporum (Dupré et al 1982, Beckjord et al 1985, Walker et al 2003, Diaz et al 2010, although Castellano & Molina (1989) noticed that some species are much more tolerant and that fertilisation effect was dependent on the application system, fertiliser type, dose and form. On the other side, Quoreshi & Timmer (2000) and Rincon et al (2007) found fertiliser doses that increased growth of containerised conifer seedling without decreasing colonisation levels of inoculated fungi from various EM species.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesised that a moderate fertilisation regime could improve morphological quality of seedlings while maintaining EM colonisation levels suitable for commercial purposes. We assess the effect of fertilisation on growth and EM status of seedlings, applying a dose similar to that used by Rincon et al (2007). We compare the effect of fertilisation on Q. ilex and Q. faginea, a faster-growing species (Sanz-Pé-rez et al 2007), and we evaluate the use of fertilisation in two inoculation methods, root-dipping and root-powdering, both applying inoculum onto roots, although with different carrier materials.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship is known to improve plant health by increasing nutrient and water uptake, alleviating environmental stresses and enhancing plant resistance against disease (Quoreshi et al, 2008;Smith and Read, 2008;Rivero et al, 2009). The importance of these mutualistic associations has gained signif icant interest due to increasing costs of irrigation and synthetic fertilisers (McKane and Kandel, 1996;Rincon et al, 2007). The natural soil biota, which includes mycorrhizal fungi, is a very important biotechnological resource and its application represents a step forward in the use of sustainable techniques for forestry production.…”
Section: Introductionmentioning
confidence: 99%